2021
DOI: 10.3389/fcimb.2021.676650
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Porcine Model of Fecal-Induced Peritonitis Reveals the Tropism of Blood Microbiome

Abstract: Recent studies have suggested the existence of a blood microbiome in the healthy host. However, changes in the blood microbiome upon bloodstream infection are not known. Here, we analyzed the dynamics of the blood microbiome in a porcine model of polymicrobial bacteremia induced by fecal peritonitis. Surprisingly, we detected bacterial populations in the bloodstream even before the infection, and these populations were maintained over time. The native blood microbiome was notably taxonomically different from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…With a presence of intra-abdominal necrotic tissue in this model, the inflammation in the peritoneal cavity affects the balance of gut microbiota, despite the inflammatory lesions being walled off. Although these data are similar to the dysbiosis in several peritonitis models, such as spontaneous bacterial peritonitis, fecal peritonitis, and peritonitis in peritoneal dialysis [ 62 , 63 , 64 ], the dysbiosis in these situations might not be only from peritonitis alone but also from the underlying overt systemic responses, including cirrhosis, sepsis, and uremia, in these situations that might affect the gut dysbiosis. Here, despite the subtle systemic responses in the cecal ligation model, the alteration in fecal dysbiosis was prominent, supporting a vulnerability of the balance in microbiota in the gut to the microenvironment [ 65 ].…”
Section: Discussionsupporting
confidence: 56%
“…With a presence of intra-abdominal necrotic tissue in this model, the inflammation in the peritoneal cavity affects the balance of gut microbiota, despite the inflammatory lesions being walled off. Although these data are similar to the dysbiosis in several peritonitis models, such as spontaneous bacterial peritonitis, fecal peritonitis, and peritonitis in peritoneal dialysis [ 62 , 63 , 64 ], the dysbiosis in these situations might not be only from peritonitis alone but also from the underlying overt systemic responses, including cirrhosis, sepsis, and uremia, in these situations that might affect the gut dysbiosis. Here, despite the subtle systemic responses in the cecal ligation model, the alteration in fecal dysbiosis was prominent, supporting a vulnerability of the balance in microbiota in the gut to the microenvironment [ 65 ].…”
Section: Discussionsupporting
confidence: 56%
“…The utility of this approach has recently been demonstrated in clinical settings, offering a new perspective for the development of biomarkers in ecology 21 24 similar to those described for several diseases in humans 16 , 20 , 25 . In fact, the existence of a blood microbiome is a concept that is now widely accepted in humans and animals, including pigs, broiler chickens, camels, cows, goats, cats and dogs 21 , 23 , 24 , 26 29 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of inflammatory diseases, Hyun et al (2021) used a faeces-induced peritonitis porcine model and revealed the emergence of new circulating bacteria after disease induction, including Escherichia/Shigella , Staphylococcus , Cloacibacterium , Diaphorobacter and Rhodanobacter [ 60 ]. Functionally, these enriched bacteria are related to ABC transporters, oxidative phosphorylation, and two-component systems [ 60 ], which may aid in the pathogenesis of peritonitis.…”
Section: Clinical Significance Of the Blood Microbiome In Human Diseasesmentioning
confidence: 99%
“…In terms of inflammatory diseases, Hyun et al (2021) used a faeces-induced peritonitis porcine model and revealed the emergence of new circulating bacteria after disease induction, including Escherichia/Shigella , Staphylococcus , Cloacibacterium , Diaphorobacter and Rhodanobacter [ 60 ]. Functionally, these enriched bacteria are related to ABC transporters, oxidative phosphorylation, and two-component systems [ 60 ], which may aid in the pathogenesis of peritonitis. Interestingly, circulating levels of the genera Escherichia/Shigella and Staphylococcus were also significantly elevated in inflammatory bowel disease (IBD, comprising ulcerative colitis and Crohn’s disease) despite the unremarkable difference in the overall blood microbiome profiles between IBD and healthy individuals [ 61 ].…”
Section: Clinical Significance Of the Blood Microbiome In Human Diseasesmentioning
confidence: 99%